2020
DOI: 10.1371/journal.ppat.1009002
|View full text |Cite
|
Sign up to set email alerts
|

The NS1 protein of the parvovirus MVM Aids in the localization of the viral genome to cellular sites of DNA damage

Abstract: The autonomous parvovirus Minute Virus of Mice (MVM) localizes to cellular DNA damage sites to establish and sustain viral replication centers, which can be visualized by focal deposition of the essential MVM non-structural phosphoprotein NS1. How such foci are established remains unknown. Here, we show that NS1 localized to cellular sites of DNA damage independently of its ability to covalently bind the 5’ end of the viral genome, or its consensus DNA binding sequence. Many of these sites were identical to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 64 publications
6
44
0
Order By: Relevance
“…Strikingly, many of these sites also coincide with TADs and contact domains that are packaged in Type A chromatin ( 35 ). In subsequent studies, Majumder and colleagues discovered that ectopically expressed viral non-structural phosphoprotein NS1 binds to cellular sites of DNA damage, and, when bound cognate sequences on the viral genome, can transport the viral genome to these cellular DDR sites [ Figure 1 ; ( 88 )]. These findings suggest that the NS1 protein of MVM, a small DNA virus, can help a viral genome navigate the nuclear milieu to essential TAD/DDR regions that promote viral infection.…”
Section: Manipulation Of 3d Genomic Architecture By Small Dna Virusesmentioning
confidence: 99%
“…Strikingly, many of these sites also coincide with TADs and contact domains that are packaged in Type A chromatin ( 35 ). In subsequent studies, Majumder and colleagues discovered that ectopically expressed viral non-structural phosphoprotein NS1 binds to cellular sites of DNA damage, and, when bound cognate sequences on the viral genome, can transport the viral genome to these cellular DDR sites [ Figure 1 ; ( 88 )]. These findings suggest that the NS1 protein of MVM, a small DNA virus, can help a viral genome navigate the nuclear milieu to essential TAD/DDR regions that promote viral infection.…”
Section: Manipulation Of 3d Genomic Architecture By Small Dna Virusesmentioning
confidence: 99%
“…NS1 protein’s various activities are regulated by protein kinase C family members phosphorylating serine residues in the protein. CPV2.NS1 like NS1 of MVM ( 56 , 62 , 63 ), H-1PV ( 15 ), and B19v ( 55 ), has been reported to induce DNA damage and cell cycle arrest in the G1 phase of the cell cycle ( 24 , 64 , 65 ). An increase in cyclin kinase inhibitors (CKIs) like p21 and p27 explains G1 arrest ( 66 ).…”
Section: Mechanisms Involved In Cpv and Ns1 Mediated Cell Deathmentioning
confidence: 99%
“…V3C-seq is based on the chromosome conformation capture sequencing technology (3C-seq) [ 122 ] used to study chromosome arrangement in the nucleus by crosslinking the sites of genomic associations and identifying these regions with sequencing. 3C-seq studies have revealed that MVM genomes become associated with DNA damage sites during early stages of infection [ 121 ]. These sites of DNA damage with associated viral genomes increase as the infection proceeds.…”
Section: Detection Of Dna Damage Dna Repair and Virus–dna Interactionsmentioning
confidence: 99%
“…V3C-seq analyses have also revealed that the viral genome association sites and DNA damage sites overlap with self-interacting genetic regions, also known as topologically associating domains (TADs) [ 52 ]. Recently, it has been shown that the localization of viral genomes to the DNA damage sites is mediated by viral NS1 [ 121 ].…”
Section: Detection Of Dna Damage Dna Repair and Virus–dna Interactionsmentioning
confidence: 99%